Structure‐guided insights on the role of NS1 in flavivirus infection. (11th March 2015) - Akey, David L.; Brown, W.Clay; Jose, Joyce; Kuhn, Richard J.; Smith, Janet L.
<x xml:space="preserve">Abstract</x> We highlight the various domains of the flavivirus virulence factor NS1 and speculate on potential implications of the NS1 3D structure in understanding its role in flavivirus pathogenesis. Flavivirus non‐structural protein 1 (NS1) is a virulence factor with dual functions in genome replication and immune evasion. Crystal structures of NS1, combined with reconstructions from electron microscopy (EM), provide insight into the architecture of dimeric NS1 on cell membranes and the assembly of a secreted hexameric NS1‐lipid complex found in patient sera. Three structural domains of NS1 likely have distinct roles in membrane association, replication complex assembly, and immune system avoidance. A conserved hydrophobic inner face is sequestered either on the membrane or in the interior of the secreted hexamer and contains regions implicated in viral replication. The exposed variable outer face is presented to cellular and secreted components of the immune system in infected patients and contains candidate regions for immune system modulation. We anticipate that knowledge of the distinct NS1 domains and assembly will lead to advances in elucidating virus‐host interactions mediated through NS1 and in dissecting the role of NS1 in viral genome replication.